Response to Alternative Media in The Development of Dakwah: An Islamic Perspective - Zainal Fadri; Akhyar Hanif (IAIN Batusangkar, 2023)
Dakwah trends get a lot of developments in the world of dakwah. In the past people proselytizing by conventional means, such as by conducting meetings and making an assessment on matters related to the value of jurisprudence and theology. But in fact, today many new media that give a different color to the model of delivering dakwah among the people. Mainstream media that can be found among them YouTube, websites, blogs and social media. Their presence is quite quickly a special concern for people who have a concentration on dakwah. Many people feel that the presence of the media can degrade the quality of dakwah delivered, but the opposite of that, the presence of these media into a dakwah progress. Everyone can gain knowledge dakwah anywhere and anytime. In this study the researcher wanted to know how the response from the public to the presence of alternative media in conveying dakwah? After that, the researcher made a mapping and views of dakwah activists about it. The method used in this research is a descriptive qualitative method that seeks to see responses from the public about alternative media, so it is expected to find a thought and answer to the community's anxiety about its presence. In this study found several responses from the public towards the development of dakwah with alternative media. Based on the community active in dakwah giving positive and negative responses. A negative response is given on the grounds that preaching through the media has a bad impact, because no one is responsible for the delivery error, then they suggest that preaching continue to be done in the normal way. Another group gave a positive response in the development of dakwah through alternative media, because it is considered more flexible, so that the teaching in the dakwah does have its limitations.